Transfer matrix approach to the hydrogen-bonding in cellulose Iα fibrils describes the recalcitrance to thermal deconstruction - Klein, Heinrich C. R.; Cheng, Xiaolin; Smith, Jeremy C.; Shen, Tongye (The journal of chemical physics, 2011)
Cellulosic biomass has the potential to serve as a major renewable energy source. However, its strong recalcitrance to degradation hampers its large-scale use in biofuel production. To overcome this problem, a detailed understanding of the origins of the recalcitrance is required. One main biophysical phenomenon leading to the recalcitrance is the high structural ordering of natural cellulose fibrils, that arises largely from an extensive hydrogen-bond network between and within cellulose polymers. Here, we present a lattice-based model of cellulose Iα, one of the two major natural forms, at the resolution of explicit hydrogen bonds. The partition function and thermodynamic properties are evaluated using the transfer matrix method. Two competing hydrogen-bond patterns are found. This plasticity of the hydrogen-bond network leads to an entropic contribution stabilizing the crystalline fibril at intermediate temperatures. At these temperatures, an enhanced probability of bonding between the individual cellulose chains gives rise to increased resistance of the entire cellulose fibril to degradation, before the final disassembly temperature is reached. The results are consistent with the available crystallographic and IR spectroscopic experiments on the thermostability of cellulose Iα.
Gesehen am 11.08.2022
Im Titel ist "α" tiefgestellt